Optimal Contest Design when the Designer's Payoff Depends on Competitive Balance - Marco Runkel (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper investigates optimal contest design when the designer's payoff is increasing in competitive balance between contestants. A two-player contest with asymmetric effort costs (asymmetric abilities) is considered. Competitive balance is measured by the difference in winning probabilities of the contestants. In contrast to previous studies, the impact of competitive balance on the optimal prize is not unique, but depends on the shape of the contest success function. Furthermore, it is shown that including competitive balance in the designer's objective may induce the designer to increase the contestants effort costs, for example, by tightening the rules of the contest.
Keywords: 330; optimal contest design; competitive balance